(untitled) (Eurasian Scientific Herald, 2022)
The paper analyzes the impact of patriotic education on ensuring national security and sustainable development of the state. The tasks assigned to patriotic education are considered. The importance and components of patriotic education are shown. The fundamental military traditions are given, which have a great educational impact on the younger generation.